2014
DOI: 10.3844/ojbsci.2014.277.285
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers in Determining Prostate Cancer Diagnosis and Prognosis

Abstract: Abstract:The clinical behavior and molecular pathology of prostate cancer is highly variable. Current "traditional" prognostic markers cannot reliably distinguish the potentially life-threatening cancer from indolent cancer. Identification of additional new predictors of cancer aggressiveness is therefore urgently required. This communication is aimed at a brief review of new biomarkers in prostate cancer diagnostics and prognostics. Pubmed systematic search was performed to collect both original and review ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Namely, S100A9 (AUC—0.957; SN 92.3%; SP 83.6%) and Annexin V (AUC—0.921; SN 90.4%; SP 80.0%) showed the greatest promise, however, Yasar et al reported no difference between serum levels of S100A8 and S100A9 in the study or control group (Yasar et al 2017 ). These markers show promise in research of prostate cancer (Novakova et al 2014 ; Grebhardt et al 2014 ). In the later study, Calprotectin serum levels were significantly elevated in the whole study group if compared to controls, although without the possibility of stratifying patients based on stage or grade.…”
Section: Proteomic Biomarkersmentioning
confidence: 99%
“…Namely, S100A9 (AUC—0.957; SN 92.3%; SP 83.6%) and Annexin V (AUC—0.921; SN 90.4%; SP 80.0%) showed the greatest promise, however, Yasar et al reported no difference between serum levels of S100A8 and S100A9 in the study or control group (Yasar et al 2017 ). These markers show promise in research of prostate cancer (Novakova et al 2014 ; Grebhardt et al 2014 ). In the later study, Calprotectin serum levels were significantly elevated in the whole study group if compared to controls, although without the possibility of stratifying patients based on stage or grade.…”
Section: Proteomic Biomarkersmentioning
confidence: 99%